The efficiency of the World Health Organization (WHO) in improving global health - Hetaf Jumaa Subhi Aburashid (International Journal of Law Research and Studies, 2025)
This study provides a comprehensive analysis of the efficiency of the World Health Organization (WHO) in improving global health. The study examines the organization's history, programs, achievements, challenges, and its impact on population health worldwide. The study concludes that the WHO has played a significant role in enhancing global health, but there are still substantial challenges facing the organization, such as funding shortages, inequality in healthcare access, and emerging public health threats. The study offers recommendations to improve the efficiency of the WHO and achieve its global health objectives.
Keywords: WHO; Health Improvement; Performance Adequacy; Performance Efficiency